IPV Perpetrator Groups: Client Engagement, and the Role of Facilitators. Issue 19 (October 2022) - Hamel, John; Buttell, Fred; Ferreira, Regardt; Roy, Valerie
Based on the emerging literature being developed in Motivational Interviewing that suggests certain group process factors and facilitator attributes predict treatment outcomes, this study sought to investigate the relationship between both client and facilitator ratings of the batterer intervention group experience. This study presents data from 16 group facilitators drawn from five agencies and 175 clients being served by these facilitators. The data gathered included both facilitator ratings of clients (i.e., Group Engagement Measure-GEM) and client ratings of facilitators and the group experience (i.e., Client Rating of Facilitator-CRF, Client Perceived Benefits of Group-CPBG). Results indicate that facilitators rated clients as being engaged in the group process across all the domains assessed by the GEM and that clients viewed the facilitators and group experiences favorably as assessed by the CRF and CPBG. There was no significant correlation between the GEM and CRF or the GEM and CPBG, but there was a strong, positive correlation between the CRF and CPBG. The results here support previous research findings suggesting a strong correlation between client engagement in the therapeutic process, based on their perception of the facilitator, and their perceived benefits of the group experience. Implications of the findings for improving empirical investigations of the batterer intervention group experience were explored and discussed.